2021
DOI: 10.1186/s40359-021-00562-1
|View full text |Cite
|
Sign up to set email alerts
|

Accomplishment of instrumental activities of daily living and its relationship with cognitive functions in adults with myotonic dystrophy type 1 childhood phenotype: an exploratory study

Abstract: Background The childhood phenotype of myotonic dystrophy type 1 (DM1) involves impaired cognitive functioning starting in infancy, which may compromise later on their ability to carry out instrumental activities of daily living (IADLs) necessary for living independently. The current study aims to document the ability to perform IADLs among adults with the childhood phenotype of DM1 and to explore its links to cognitive functioning. Methods This cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Multiple factors play an essential role in contributing to the variations in cognitive status among these forms, including the length of the CTG repeat expansion in the DMPK gene, age at onset, and inheritance pattern ( Palmer et al, 1994 ; Winblad et al, 2006 , 2016 ; Tremblay et al, 2021 ). An earlier onset and longer disease duration both indicate more severe cognitive deficits.…”
Section: Cognitive Impairment In Dmmentioning
confidence: 99%
“…Multiple factors play an essential role in contributing to the variations in cognitive status among these forms, including the length of the CTG repeat expansion in the DMPK gene, age at onset, and inheritance pattern ( Palmer et al, 1994 ; Winblad et al, 2006 , 2016 ; Tremblay et al, 2021 ). An earlier onset and longer disease duration both indicate more severe cognitive deficits.…”
Section: Cognitive Impairment In Dmmentioning
confidence: 99%
“…Additionally, social cognition has also been studied in DM1, and it is suggested that while patients don't show difficulties in social cognition tasks that demand higher cognitive processes, such as Theory of Mind, they perform worse on less cognitively demanding social cognition tasks, such as facial emotion recognition [25]. This cognitive impairment could be reflected in the observed functional disability and dependency in daily activities [26,27]. On average people with cognitive symptoms show lower social engagement, more psychosocial problems, and poorer psychosocial well-being [28,29].…”
Section: Cognitive Symptoms In Dm1mentioning
confidence: 99%
“…Although previous studies have examined longitudinal cognitive changes in DM1, the declines over time in this population remain unclear. Since cognitive function is associated with a patient's participation, independence, and quality of life [17][18][19][20], identifying the longitudinal course of cognitive impairment may contribute to plans for support and interventions [21]. Therefore, further evidence of longitudinal changes in cognitive functioning in patients with DM1 is essential to improve our understanding of cognition in DM1.…”
Section: Introductionmentioning
confidence: 99%